2020
DOI: 10.1017/s0950268820002563
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of COVID-19 transmission including indirect transmission mechanisms: a mathematical analysis

Abstract: The outbreak of the novel coronavirus severe acute respiratory syndrome-coronavirus-2 has raised major health policy questions and dilemmas. Whilst respiratory droplets are believed to be the dominant transmission mechanisms, indirect transmission may also occur through shared contact of contaminated common objects that is not directly curtailed by a lockdown. The conditions under which contaminated common objects may lead to significant spread of coronavirus disease 2019 during lockdown and its easing is exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 15 publications
(32 reference statements)
2
28
0
2
Order By: Relevance
“…According to a recent systematic review, in household settings, contamination of patients’ surroundings was as high as 14%, with patients’ utensils, electronic high-touch surfaces, beds, and floors representing the most frequently contaminated surfaces [ 80 ]. Finally, since fomite transmission is difficult to prove, some publications used mathematical models to demonstrate the contribution of fomites to the growth of the epidemic via transmission, underscoring the need for awareness of this important aspect of transmission [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent systematic review, in household settings, contamination of patients’ surroundings was as high as 14%, with patients’ utensils, electronic high-touch surfaces, beds, and floors representing the most frequently contaminated surfaces [ 80 ]. Finally, since fomite transmission is difficult to prove, some publications used mathematical models to demonstrate the contribution of fomites to the growth of the epidemic via transmission, underscoring the need for awareness of this important aspect of transmission [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although different studies have identified the survival characteristics of SARS-CoV-2 on surfaces, such as stainless steel, plastic, glass, etc. [19][20][21], no evidence of fomite transmission has been found yet at the current state of research [22] and its potential as transmission route was considered low by Mondelli et al [23]. • via small aerosols (characterised by a diameter lower than 5-10 μm) [24].…”
Section: Transmission Routes 31mentioning
confidence: 98%
“…The average time from exposed to infectious state is taken to be D e = 4 days, and the characteristic time during which an individual is infectious is taken to be D i = 5 days. A mean infected fatality ratio 0.0050 is adopted (Meiksin, 2020;PHAS, 2020). Estimates for the mean lag time from onset of the infection to death range from 19 to 22 days (Davies et al, 2020;Flaxman et al, 2020).…”
Section: Seir Equations With a Fomite Termmentioning
confidence: 99%
“…To give the limits on N f some context, the mean number C f of potentially contaminatable objects a person may come into contact with per day must be specified. An estimate for the post is C f 0.57 d −1 person −1 (Meiksin, 2020).…”
Section: Parameter Constraintsmentioning
confidence: 99%